Features of physical development and somatotype of girls and women involved in fitness - L.V. Podrigalo; H.P. Artemieva; O.A. Rovnaya; N.S. Misevra; Zh.V. Sotnikova-Meleshkina; A.P. Podavalenko; K.M. Sokol; I.Yu. Robak (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose : Comparative analysis of the physical development features and somatotype of girls and women involved in fitness. Material : The experiment involved 95 girls and women, divided into 2 groups. Group 1 - 48 girls (36.04 ± 0.19) years, Group 2 - 47 women (43.26 ± 0.22) years, (p <0.01). Participants practiced fitness 2-3 times a week. The duration of the training was 60 minutes. It was determined the body mass and body length, wrist circumference, waist and hips circumferences. The TANITA BC 587 analyzer was applied to determine muscle and fat mass, the specific weight of fat tissue, water content, percentage of visceral fat, basal metabolism value, bone mass mineralization. It was calculated the body mass index and the waist-to-hip ratio. The results were evaluated applying the Student's t-test (t) and Rosenbaum (Q) and Wilcoxon - Mann - Whitney (U) criteria. Results : There were no significant differences in body length and body mass. The girls confirmed a less value of hip circumference (t = 2.04, p <0.05) and a tendency to less waist circumference (t = 1.97, p <0.1) in comparison with group 2. The participants of group 2 had a larger wrist circumference (U = 891, p <0.05). According to this parameter, persons with asthenic body type prevailed among participants. Their specific weight was (56.25 ± 7.16)% of group 1 and (53.19 ± 7.28)% of group 2. It was confirmed less absolute body fat content in group 1 (t = 2.09, p <0.05). All participants were characterized by larger muscle mass. There were no differences in this parameter between groups. It was determined the high concentration of specific weight of fat tissue in comparison with age standards. The content of visceral fat was within the age norm. Its content was higher in group 2 (Q = 18, p <0.01). The basal metabolic value was larger in group 2 (Q = 17, p <0.01). The values of bone mass mineralization reflect the correspondence to the body mass of the participants. This parameter did not have significant differences in the groups. The body mass index value in group 1 was within the average interval. In group 2, this index was higher than the standard one. The body mass index in group 1 was significantly lower (t = 2.18, p <0.05). The participants with a body mass index above the norm were (35.42 ± 6.90)% of group 1 and (59.57 ± 7.16)% of group 2. The prevalence of waist-to-hip ratio above the norm was (54.17 ± 7.19)% 1 group and (59.57 ± 7.17)% 2 group, (p> 0.05). Conclusions : it was determined the proximity of the main anthropometric parameters (mass and body length). The girls have lower values of the hip circumference. Persons with asthenic body type prevailed among the participants. Analysis of the indices confirmed the high prevalence of overweight and high risk of developing metabolic syndrome. The application of bio-impedance method confirmed and clarified the results of anthropometric research. The participants demonstrated the increased content of subcutaneous and visceral fat, increasing with age. The water level in the body gradually decreases with age. This is considered as a reflection of age-related physiological changes in metabolism and should be considered in fitness training organizing. Studies have confirmed the informativeness and adequacy of the bio-impedance method.